Arterial thromboembolism in a cat with transient myocardial thickening - Vollmar, C.; Mitropoulou, A.; Hassdenteufel, E.; Hildebrandt, N.; Schneider, M.; Justus Liebig University Giessen (My University, 2024)
Feline arterial thromboembolism has been reported to be secondary to various feline cardiomyopathies; however, it has not been described in cats with transient myocardial thickening. A previously healthy, one-year-old, castrated male cat presented with acute paraparesis and congestive heart failure. Echocardiography revealed asymmetric left ventricular free wall thickening and left atrial enlargement. Antithrombotic treatment and cardiac medication resulted in reperfusion and mobility on day seven in one limb and on day 10 in the other. Different complications were managed successfully, including worsening acute kidney injury, inflammation, pleural effusion, and anemia. After three weeks, the cat was discharged and prescribed oral antithrombotic drugs (clopidogrel and rivaroxaban) and cardiac medication. Within five months, echocardiographic findings normalized, and medical treatment was gradually discontinued. To date, the cat remains healthy at 1735 days after the initial diagnosis and 1494 days after the last antithrombotic medication. To the best of our knowledge, this is the first case report on feline arterial thromboembolism combined with transient myocardial thickening, with favorable long-term survival.
Keywords: ddc:630